2022
DOI: 10.3389/fendo.2022.918652
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Attenuates Post-Inflammatory IBS-Associated Visceral and Somatic Hypersensitivity and Correlates With the Regulatory Mechanism of Epac1–Piezo2 Axis

Abstract: Electroacupuncture (EA) is considered to have a therapeutic effect in the relief of irritable bowel syndrome (IBS)-associated visceral hypersensitivity via the reduction of the level of 5‐hydroxytryptamine (5‐HT) and 5-HT3 receptors (5-HT3R). However, whether Epac1/Piezo2, as the upstream of 5-HT, is involved in this process remains unclear. We investigated whether EA at the ST36 and ST37 acupoints alleviated visceral and somatic hypersensitivity in a post-inflammatory IBS (PI-IBS) model mice via the Epac1-Pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…However, due to the characteristics of multi-link and multi-target of acupuncture, there is still a lack of in-depth understanding of the mechanisms associated with acupuncture in the treatment of IBS. Relative studies had confirmed that acupuncture can improve visceral hypersensitivity and intestinal motility by regulating the Epac1-Piezo 2 axis and reducing 5-HT and 5-HTR expressions ( Zhao et al, 2016 ; Guo et al, 2022 ) and regulate the brain-gut axis and nervous system by affecting neurotransmitters including 5-HT, substance P, calcitonin gene-related peptide, nitric oxide, and norepinephrine. In addition, IL-18, IL-23, TNF-α, mast cells, and other immune cells and inflammatory factors may be also involved in the regulation of IBS by acupuncture ( Wu et al, 2008 ; Ma et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the characteristics of multi-link and multi-target of acupuncture, there is still a lack of in-depth understanding of the mechanisms associated with acupuncture in the treatment of IBS. Relative studies had confirmed that acupuncture can improve visceral hypersensitivity and intestinal motility by regulating the Epac1-Piezo 2 axis and reducing 5-HT and 5-HTR expressions ( Zhao et al, 2016 ; Guo et al, 2022 ) and regulate the brain-gut axis and nervous system by affecting neurotransmitters including 5-HT, substance P, calcitonin gene-related peptide, nitric oxide, and norepinephrine. In addition, IL-18, IL-23, TNF-α, mast cells, and other immune cells and inflammatory factors may be also involved in the regulation of IBS by acupuncture ( Wu et al, 2008 ; Ma et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…IBS patients all experience 5-HT-induced nociceptive responses ( Keszthelyi et al, 2015 ), and Piezo2 channels can induce 5-HT release when activated by mechanical stimuli ( Alcaino et al, 2018 ). Therefore, Piezo2 in the colon is closely related to 5-HT ( Guo et al, 2022 ).…”
Section: Expression and Function Of Piezo Channels In Gi Diseasesmentioning
confidence: 99%
“…Moreover, in adult patients with constipation dominant-IBS (IBS-C), an RCT comparing EA to mild-warm moxibustion treatment at ST25 and ST37 showed improvement of defecation frequency compared to baseline up to three months after treatment, and the effects of EA were proposed to be mediated through alleviation of visceral hypersensitivity and improved brain-gut function as visualised with fMRI ( 185 ). Additionally, several studies in animals and humans show altered levels of stress hormones such as cortisol and epinephrine, and changes in 5-HT associated with acupuncture, although mostly in the context of visceral pain management ( 186 189 ). In mice and rats with IBS-associated visceral hypersensitivity, treatment with EA significantly reduced 5-HT and 5-HT receptor mRNA expression levels compared to sham-treatment and was associated with attenuated visceral hypersensitivity ( 186 , 187 ).…”
Section: Acupuncture and Experimental Studies: Proposed Mechanismsmentioning
confidence: 99%
“…Additionally, several studies in animals and humans show altered levels of stress hormones such as cortisol and epinephrine, and changes in 5-HT associated with acupuncture, although mostly in the context of visceral pain management ( 186 189 ). In mice and rats with IBS-associated visceral hypersensitivity, treatment with EA significantly reduced 5-HT and 5-HT receptor mRNA expression levels compared to sham-treatment and was associated with attenuated visceral hypersensitivity ( 186 , 187 ). In the context of obesity, a potential role for 5-HT on thermogenesis of brown adipose tissue in mice has been reported ( 189 ) and gut microbiota are directly implicated in the process of peripheral 5-HT biosynthesis in their host, both animals and human adults with obese phenotypes ( 122 , 190 , 191 ).…”
Section: Acupuncture and Experimental Studies: Proposed Mechanismsmentioning
confidence: 99%